Investigation of the Interaction Between Dr5-As Long Noncoding Rna and Caprin1 Protein - Akgül, Bünyamin; Kaçar, Vahide İlayda (Izmir Institute of Technology, 2022)
Cell proliferation is the crucial process for many physiological incidents such as tissue and organ development, wound healing, and immune system reactions. It is achieved by the growth and division of cells in a multicellular organism. Investigation of molecules involved in the regulation of cell cycle mechanism provides insight into reasons and treatments of the diseases such as cancer. In recent years, information that acquired from deep sequencing reveals that several proteins and non-coding RNAs have crucial role in the regulation of cell cycle and proliferation. Death receptor 5 antisense (DR5-AS) is a novel long non-coding RNA (lncRNA) transcript that is cisplatin inducible and is involved in modulation of cell proliferation and cell cycle in HeLa cells. When DR5-AS lncRNA was knocked down, the morphology of HeLa cells became spherical without inducing apoptosis. Although this lncRNA reduces cell proliferation via a cell cycle arrest at S and G2/M phases, mechanism behind this cell cycle arrest is not known. lncRNAs work in complexes with RNA, DNA, and protein interactions in the cell. There are several experimental and bioinformatical approaches to investigate RNA: protein interactions such as PAR-CLIP. In this approach, proximal protein and RNAs are covalently bonded with UV radiation. Then this complex is immunoprecipitated with specific antibodies. According to PAR-CLIP data of DR5-AS lncRNA, CAPRIN1 is a cell cycle associated protein that has the highest interaction score. The results suggest that CAPRIN1 and DR5-AS work reversely in cell proliferation although under the cisplatin treatment, CAPRIN1 enhances the expression of DR5-AS lncRNA. All these observations were confirmed by many quantitative experiments. Conclusively, this study provides a clue about how DR5-AS lncRNA might regulate cell cycle and proliferation through CAPRIN1 protein.

Hücre proliferasyonu, doku ve organ gelişimi, yaraların iyileşmesi ve bağışıklık sistemi reaksiyonları gibi birçok fizyolojik olay için çok önemli bir hücresel işlevdir. Çok hücreli bir organizmada hücrelerin büyümesi ve bölünmesi işlemidir. Hücre döngüsü mekanizmasının düzenlenmesinde görev alan moleküllerin araştırılması kanser gibi hastalıkların nedenlerinin ve tedavilerinin anlaşılmasını sağlar. Son yıllarda, derin sekanslamadan elde edilen bilgiler, birçok proteinin ve kodlamayan RNA'nın hücre döngüsü ve proliferasyonun düzenlenmesinde önemli bir role sahip olduğunu ortaya koymaktadır. DR5-AS, sisplatin ile indüklenebilir kodlamayan bir RNA transkripsiyonudur ve HeLa hücrelerinin hücre proliferasyonu ve hücre döngüsünde bir modülatör olarak yer alırken, DR5-AS lncRNA susturulduğunda, HeLa hücresinin morfolojisi apoptozu indüklemeden küresel hale gelir. Bu lncRNA, S ve G2/M fazlarında hücre döngüsü durdurma yoluyla hücre çoğalmasını azaltmasına rağmen, bu hücre döngüsü durdurmasının arkasındaki mekanizma bilinmemektedir. lncRNA'lar hücrede RNA, DNA ve protein etkileşimleri ile çalışır. RNA: protein etkileşimlerini araştırmak için PAR-CLIP gibi birkaç deneysel ve biyoinformatik yaklaşım vardır. Bu yaklaşımda, birbiriyle etkileşecek kadar yakın olan protein ve RNA'lar UV radyasyonu ile kovalent olarak bağlanır. Daha sonra bu kompleks, spesifik antikorlarla çöktürülür. DR5-AS lncRNA'nın PAR-CLIP verilerine göre CAPRIN1, en yüksek etkileşim skoruna sahip, hücre döngüsü ile ilişkili bir proteindir. Sonuçlar, sisplatin uygulaması altında CAPRIN1'in DR5-AS lncRNA ekspresyonunu arttırmasına rağmen, CAPRIN1 ve DR5-AS'nin hücre proliferasyonunda tersine çalıştığını göstermektedir. Tüm bu gözlemler qPCR ile doğrulanmıştır. Sonuç olarak, bu çalışmada, DR5-AS lncRNA'nın CAPRIN1 proteini aracılığıyla hücre döngüsünü ve proliferasyonu düzenlediğine dair oldukça önemli veriler sunulmaktadır.
DR5-AS uzun kodlamayan RNA'sının CAPRIN1 proteini ile etkileşiminin araştırılması
Thesis (Master)--Izmir Institute of Technology, Molekular Biology and Genetics, Izmir, 2022
Includes bibliographical references (leaves. 33-38)
Text in English; Abstract: Turkish and English
Keywords: Cell cycle; Cell proliferation; Long non-coding RNAs; CAPRIN1